2021
DOI: 10.1108/jeim-06-2020-0233
|View full text |Cite
|
Sign up to set email alerts
|

Can we trust AI? An empirical investigation of trust requirements and guide to successful AI adoption

Abstract: Purpose Artificial intelligence (AI) fosters economic growth and opens up new directions for innovation. However, the diffusion of AI proceeds very slowly and falls behind, especially in comparison to other technologies. An important path leading to better adoption rates identified is trust-building. Particular requirements for trust and their relevance for AI adoption are currently insufficiently addressed.Design/methodology/approachTo close this gap, the authors follow a qualitative approach, drawing on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(53 citation statements)
references
References 51 publications
2
44
0
Order By: Relevance
“…For example, UTAUT is used in analyzing the adoption of AI tools (Venkatesh, 2021), the technology acceptance model (TAM) is used in AI adoption in the hospitality industry (Pillai & Sivathanu, 2020), and TAM–technology–organizations–environment is used in AI adoption in manufacturing firms (Chatterjee et al, 2021). The role of trust in AI adoption is studied using the valence framework (Bedué & Fritzsche, 2021), and AHP is used in analyzing barriers to AI adoption in healthcare (Al Badi et al, 2021). Reputed theories like UTAUT and TAM predict adoption behavior.…”
Section: Discussionmentioning
confidence: 99%
“…For example, UTAUT is used in analyzing the adoption of AI tools (Venkatesh, 2021), the technology acceptance model (TAM) is used in AI adoption in the hospitality industry (Pillai & Sivathanu, 2020), and TAM–technology–organizations–environment is used in AI adoption in manufacturing firms (Chatterjee et al, 2021). The role of trust in AI adoption is studied using the valence framework (Bedué & Fritzsche, 2021), and AHP is used in analyzing barriers to AI adoption in healthcare (Al Badi et al, 2021). Reputed theories like UTAUT and TAM predict adoption behavior.…”
Section: Discussionmentioning
confidence: 99%
“…(2020, p. 286) also pointed out that trust is the most significant predictor of m-commerce adoption, as it strongly determines its success. In addition, Bedué and Fritzsche (2021) showed that an important path leading to better AI-based adoption is trust-building, which is why we chose to trust as a main psychological factor (organism) in the model.…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 99%
“…While there is great appreciation for the potential of AI to revolutionize organizations, there is still some uncertainty about its consequences on people and organizations ( Bedué and Fritzsche, 2021 ). Frick (2015) said, “as these machines evolve from tools to teammates, one thing is clear: Accepting them will be more than simply adopting new technology.” In collaborative initiatives, the acceptance or avoidance of AI is dependent on the perception of AI.…”
Section: Proposed Conceptual Model and Hypothesis Developmentmentioning
confidence: 99%